Student transcription for reflective language learning. (14th April 2018) - Cowie, Neil
Abstract: Transcribing is a well-established technique that allows language students to analyse their own conversations and recorded talks. In the past it may have been difficult for a teacher to organize transcription by all students in one class on a regular basis but with the use of digital technology it is now relatively easy for students to transcribe their own talks and online recordings. This study describes procedures for carrying out these tasks in a Japanese university English listening course. From an analysis of the student reflective comments various categories emerge including dealing with difficult sounds and unknown words, listening and speaking strategy use, and peer-recommended listening websites. Using the framework of exploratory practice, these student insights are recycled by the teacher into subsequent lessons. This cycle of transcription, reflection, and feedback acts as an authentic source for student concerns about how to improve their conversational and listening skills.